Material Development Of Electronic Book (BSE) Contextual Teaching And Learning Bahasa Inggris SSMP To Develop Students' Communicative Competence - Kurniasari., Fistantia Lulus, Drs. Djoko Srijono, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This study is intended to find out the task in Contextual Teaching and Learning Bahasa Inggris SMP electronic book. The objective of this study is to describe what extent tasks in the electronic book develop students' communicative competence. In achieving the objective, the writer uses descriptive qualitative as the method in collecting and analyzing the data. The object of the research is the tasks including in the electronic book. The data arc analyzed by using theory of communicative competence proposed by Celce-Murcia, et al. The result of this research shows that the tasks in the electronic book are sufficient to develop students' communicative competence. In developing students' discourse competence, there are sufficient tasks in this electronic book- This electronic book is also provided sufficient tasks to develop students' linguistic competence. To develop students' actional competence, this electronic book has sufficient task. Unfortunately, this electronic book does not provide suffrcient task both in developing socio-cultural and strategic competence-Although there are two competences which are not sufficient, but there are three competences which are sufficient to develop students' communicative competence. Thus, the writer considers the fasks in this electronic book is sufficient to develop students' communicative competence.